Endorphin Massage Training for a Group of Postpartum Women to Accelerate Uterine Involution (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2024)
The postpartum period is the birth period that begins after the birth of the baby until the organs recover as they were before birth. One of the physical changes that occurs in the reproductive system is the process of uterine involution. If the involution process does not go well, it will cause postpartum complications. One way to speed up the uterine involution process is with endorphin massage. Postpartum mothers' knowledge regarding the benefits of endorphin massage is still lacking. This was found in Teruna Sari Hamlet, Dauh Puri Kaja Village. The role of midwives is needed to provide education and training regarding the benefits of endorphin massage. This training was carried out in Teruna Sari Hamlet, Dauh Puri Kaja Village using poster media. The targets for this community service are 15 postpartum mothers. Activities run well and smoothly. After being given education and training regarding the benefits of endorphin massage, it was discovered that the participants understood better and several postpartum mothers were enthusiastic and wanted to practice it at home. Midwives and posyandu cadres who are used as a place for service said they would introduce endorphin massage to postpartum women to speed up the reduction in uterine involution.
Keywords: Training; Endorphin Massage; Postpartum Mothers